1997
DOI: 10.1093/brain/120.6.1027
|View full text |Cite
|
Sign up to set email alerts
|

The temporal variant of frontotemporal dementia

Abstract: Frontotemporal dementia is a dementia syndrome with diverse clinical characteristics. Based upon clinical parameters and single photon emission computed tomography, we identified 47 frontotemporal dementia subjects. In 10 of these 47 the primary site of brain dysfunction was anterior temporal and orbital-frontal with other frontal regions relatively spared. In this temporal lobe variant (TLV) of frontotemporal dementia, five of the subjects had more severe left-sided, and five had more right-sided, hypoperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
254
2
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 377 publications
(289 citation statements)
references
References 30 publications
22
254
2
6
Order By: Relevance
“…It is worth noting that, with the evolution of the disease, SD patients develop executive dysfunction and behavioural symptoms [18], in accordance with the role of the frontal lobes in behaviour regulation.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…It is worth noting that, with the evolution of the disease, SD patients develop executive dysfunction and behavioural symptoms [18], in accordance with the role of the frontal lobes in behaviour regulation.…”
Section: Introductionsupporting
confidence: 54%
“…SPECT has been used in few studies to investigate the patterns of regional cerebral blood flow in SD. The results of these studies have principally demonstrated temporal bilateral or left involvement [32,71] or temporal and frontal bilateral involvement [18]. PET has a better spatial resolution and quantitative accuracy than SPECT, and appears to be a more promising functional imaging technique for the diagnosis and differential diagnosis of dementia [30].…”
Section: Functional Neuroimaging Methods Such As Single Photon Emissimentioning
confidence: 99%
See 3 more Smart Citations